2004
DOI: 10.1097/01.mlr.0000102367.93252.70
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Groups (CRGs)

Abstract: CRGs performance is comparable to other risk adjustment systems. CRGs have the potential to provide risk adjustment for capitated payment systems and management systems that support care pathways and case management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
0
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(101 citation statements)
references
References 2 publications
0
89
0
12
Order By: Relevance
“…38 Chronic conditions are defined as physical, mental, emotional, behavioral or developmental disorders, expected to last at least 12 months, or having sequelae that last at least 12 months, and that require ongoing treatment and/or monitoring. All CRGs can be folded into 9 CRG statuses.…”
Section: Methodsmentioning
confidence: 99%
“…38 Chronic conditions are defined as physical, mental, emotional, behavioral or developmental disorders, expected to last at least 12 months, or having sequelae that last at least 12 months, and that require ongoing treatment and/or monitoring. All CRGs can be folded into 9 CRG statuses.…”
Section: Methodsmentioning
confidence: 99%
“…1 Likewise, Hughes et al found that in 1998, Medicare's sickest 15.3% of patients accounted for 75.7% of expenditure. 2 In the United Kingdom, the Department of Health reports that around 5% of patients account for 40% of inpatient bed-days. 3 South Auckland Health 4 reports that in 2001, 14% of patients accounted for 44% of adult medical bed-days (national data are not available in New Zealand).…”
Section: Introductionmentioning
confidence: 99%
“…CRG classifies people into one of the following health states: 1) Healthy; 2) Significant acute illness; 3) Single or multiple minor chronic disease; 4) Moderate chronic diseases; 5) Chronic dominant diseases; 6–7) Multiple dominant chronic diseases; 8) Advanced neoplastic disease; 9) Catastrophic diseases. Its purpose, among others, is to detect diseases requiring greater attention, to monitor prevalence rates of chronic diseases, to understand the patterns of use and consumption of services and to develop risk and price adjustment applications [25]. …”
Section: Theory and Methodsmentioning
confidence: 99%